Analisis Kepribadian Kim Ji Young Dalam Budaya Patriarki: Analisis Teori Sigmund Freud Dalam Film “Kim Ji Young, Born 1982” - Heri Isnaini; Sifa Khaerunnisa; Kalyska Khusnul Khotimah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This study aims to explore an in-depth understanding of Kim Ji Young's personality in the film "Kim Ji Young, Born 1982" in the context of patriarchal culture using Sigmund Freud's psychoanalytic theory. The research method used is a qualitative method using note-taking technique. We used Sigmund Freud's theory, specifically concepts such as id, ego, and superego, to help us understand the inner conflict experienced by the main character. We also analyzed various events in the film that depict Kim Ji Young's experience as a woman in a society dominated by patriarchal values. The results of this study show that Kim Ji Young experiences complex internal conflicts while performing her role as a woman in a patriarchal culture. Freud's theory helps us understand how these conflicts arise and affect her personality. In addition, this study also emphasizes the important role of family environment, society, and childhood experiences in shaping Kim Ji Young's personality. This research has important implications in understanding the role of women in a patriarchal society and how psychoanalytic theory can be used to analyze characters in works of art such as films.